520 Diagnosis and Treatment Peculiarities in an Infant with Bleeding Disorder. (October 2012) - Iurian, SI; Neamtu, ML; Gradinariu, G; Iurian, S; Vidrighin, A; Vina, E
Abstract : Background and Aims: One of bleeding causes due to vitamin K deficiency is gut flora destruction secondary to antibiotic treatment early in life. Authors emphasize diagnosis and treatment difficulties for an infant with massive uncontrolled bleeding. Methods: Authors present a 5 weeks-old breastfed infant transferred in pediatric clinic for severe anaemia. Family history: healthy parents, no consanguinity. Case history: recent respiratory infection treated with antibiotics; no recent trauma or surgery. Clinical exam: skin pallor, petechiae, ecchymoses, jaundice, huge haematoma (20/14 cm), wide-spread from neck to lumbar area. Results: Blood investigations: severe anaemia (Hb=3.5g/dl), severe hyponatremia, normal liver function, negative serology for celiac disease. Negative test for cystic fibrosis. Hemostasis evaluation: normal values for bleeding time, platelets and fibrinogen; significant prolongation for prothrombin time and activated partial thromboplastin time. Evolution: Infant developed fulminant seizures secondary to hyponatremia and bleeding at venous puncture sites, justifying urgent initiation of anticonvulsant therapy and recombinant human coagulation factor VII, even before first hemostasis evaluation. Despite of therapy, bleedings symptoms persisted and became more severe. According to hemostasis investigations, we diagnosed vitamin K deficiency and we reconsidered the treatment using K vitamin. Prompt improvement of bleeding after vitamin K therapy confirmed vitamin K deficiency. After blood transfusion authors noticed haemoglobin(Hgb) improvement (at discharge Hgb=14.1 g/dl). Conclusions Authors emphasize diagnosis and treatment difficulties in an infant with severe bleeding because of vitamin K deficit; In cases with severe bleeding, it's mandatory to consider vitamin K treatment; Antibiotic treatment should be carefully considered in infants.